2019
DOI: 10.3390/s19184044
|View full text |Cite
|
Sign up to set email alerts
|

UWB/Binocular VO Fusion Algorithm Based on Adaptive Kalman Filter

Abstract: Among the existing wireless indoor positioning systems, UWB (ultra-wideband) is one of the most promising solutions. However, the single UWB positioning system is affected by factors such as non-line of sight and multipath, and the navigation accuracy will decrease. In order to make up for the shortcomings of a single UWB positioning system, this paper proposes a scheme based on binocular VO (visual odometer) and UWB sensor fusion. In this paper, the original distance measurement data of UWB and the position i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Even though there is a clear trade-off between positioning accuracy and number of visual odometer restarts (the higher the first the more restarts are necessary), our initial accuracy goal (∼5 cm) was fulfilled. We have also demonstrated that, in this scenario, our approach keeps the benefits of visual odometry by correcting it with UWB data, outperforming the Kalman fusion in [25] in case visual odometry fails, both in terms of stopping point accuracy and path RMSE.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Even though there is a clear trade-off between positioning accuracy and number of visual odometer restarts (the higher the first the more restarts are necessary), our initial accuracy goal (∼5 cm) was fulfilled. We have also demonstrated that, in this scenario, our approach keeps the benefits of visual odometry by correcting it with UWB data, outperforming the Kalman fusion in [25] in case visual odometry fails, both in terms of stopping point accuracy and path RMSE.…”
Section: Discussionmentioning
confidence: 81%
“…Direct CTRA Kalman fusion performed better than CTRA Kalman fusion based on linear combinations of sensor readings as in [25] if the RealSense unit worked correctly. Also in that case, the results of these two variants were superior to CTRA Kalman-filtered Pozyx data, reflecting the beneficial effect of RealSense data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings from the study indicated that this method had a higher positioning accuracy compared with that of the traditional federated EKF method. A sensor fusion scheme based on binocular visual odometer (VO)/UWB was previously reported (Zeng et al, 2019 ). In the study, the adaptive Kalman filtering method was used to fuse the UWB raw distance measurement data and the binocular VO position information.…”
Section: Introductionmentioning
confidence: 99%